Environmental controls on isolated convection in the Amazon: an observational and numerical modeling study - Viscardi, Leandro Alex Moreira (2023)
The Amazon rainforest is a vital component of the global climate system, playing a significant role in the hydrological and energy cycles. The intense convection in this region influences atmospheric circulation on a global scale and drives large-scale transports of energy and moisture, with implications for potential climate change pathways. Despite its importance, understanding and simulating the shallow-to-deep (STD) convective transition in this region has been a long-standing challenge. This is partially due to the wide range of spatial and temporal scales involved and the complexity of cloud physical processes and biosphere-atmosphere interactions. In this study, we combined recent observations and high-resolution simulations to evaluate the triggering mechanisms and assess the relative importance of different environmental controls on locally-driven convection in the Amazon. Observationally, we evaluated the environmental conditions associated with shallow, congestus, and isolated deep convection days during the wet season (December to April), employing data from the GoAmazon (2014-2015) experiment. The deep regime is characterized by moister conditions in low levels during the morning and strong moisture convergence in the afternoon. In contrast, shallow and congestus days are drier and dominated by moisture divergence in the morning. The peak of precipitation associated with the STD transition occurs around 16-17 local standard time. Afternoon precipitation, on average, increases with integrated column water vapor, low-level wind shear, and convective available potential energy; but relatively higher values of these parameters do not necessarily guarantee that the STD transition will occur. Numerically, we conducted simulations during the period of December 2014, utilizing large-scale forcing specifically developed for the GoAmazon2014/5 experiment. The model consistently reproduced the observations for precipitation, moisture, and surface fluxes of radiation, latent and sensible heat. Through sensitivity experiments, we examined the relative importance of moisture and vertical wind shear in controlling the STD convective transition. We found that deep convection in the Amazon region is highly sensitive to low-level environmental conditions. Notably, early morning low-level preconditioning is vital to daytime convection and precipitation. Only unrealistically dry conditions in the free troposphere effectively inhibit the development of deep convection. The large-scale field of vertical moisture advection strongly impacts the development of convection, which is indirectly linked to water vapor convergence. Low-level wind shear facilitates the STD transition under moderate strength, although it can still occur even in the absence of wind shear or under strong wind shear conditions. The upper-level wind shear negatively impacts high cloud formation, but this impact is relatively minor compared to that associated with low-level wind shear. The synergy between observations and high-resolution simulations provided a comprehensive analysis with crucial quantitative information on the environmental controls of isolated convection. Our findings contribute to advancing our comprehension of tropical convection and provide valuable guidance for future research aimed at enhancing weather and climate models.